Connecting - Helen Walker; Grace Feuerverger; Gesa E. Kirsch; Betsy Newmeyer; Anita Voelker; Allison Brimmer; Debbie Axelrod; Margo Wilson; Catherine M. Nelson; Liang Zhao (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
Connecting Helen Walker - Growing Up Grace Feuerverger - Mandy Gesa E. Kirsch - A Teaching Success or Failure? Betsy Newmeyer - My RIF’d Life Anita Voelker - Will’s Story Allison Brimmer - Elitist White Lady Who Tries Too Hard Debbie Axelrod - Dear Professor Walker Margo Wilson - Burnishing the Bruises Catherine M. Nelson - Jimmy Liang Zhao - Lead by Example